Influence of a combined CT/C-arm system on periprocedural workflow and procedure times in mechanical thrombectomy - Pfaff, Johannes; Schönenberger, Silvia; Herweh, Christian; Pham, Mirko; Nagel, Simon; Ringleb, Peter A.; Heiland, Sabine; Bendszus, Martin; Möhlenbruch, Markus Alfred (European radiology, 2017)
ObjectiveTo achieve the fastest possible workflow in ischaemic stroke, we developed a CT/C-arm system, which allows imaging and endovascular treatment on the same patient table.MethodsThis prospective, monocentric trial was conducted between October 2014 and August 2016. Patients received stroke imaging and mechanical thrombectomy under general anaesthesia (GA) or conscious sedation (CS) using our combined setup comprising a CT-scanner and a mobile C-arm X-ray device. Primary endpoint was time between stroke imaging and groin puncture. We compared periprocedural workflow and procedure times with the literature and a matched patient cohort treated with a biplane angiographic system before installation of the CT/C-arm system.ResultsIn 50 patients with acute ischaemic stroke due to large-vessel occlusion in the anterior circulation, comparable recanalization rates were achieved by using the CT/C-arm setup (TICI2b-3:CT/C-arm-GA: 85.7%; CT/C-arm-CS: 90.9%; Angiosuite: 78.6%; p = 0.269) without increasing periprocedural complications. Elimination of patient transport resulted in a significant reduction of the time between stroke imaging and groin puncture: median, min (IQR): CT/C-arm-GA: 43 (35-52); CT/C-arm-CS: 39 (28-49); Angiosuite: 64 (48-74); p < 0.0001.ConclusionThe combined CT/C-arm system allows comparable recanalization rates as a biplane angiographic system and accelerates the start of the endovascular stroke treatment. Key Points • The CT/C-arm setup reduces median time from stroke imaging to groin puncture.• Mechanical thrombectomy using a C-arm device is feasible without increasing peri-interventional complications.• The CT/C-arm setup might be a valuable fallback solution for emergency procedures.• The CT/C-arm setup allows immediate control CT images during and after treatment.
Gesehen am 17.09.2018